1987
DOI: 10.1161/01.str.18.2.441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ketamine on cerebral cortical blood flow and metabolism in rabbits.

Abstract: The effects of intravenous ketamine (1 mg/kg) on cerebral cortical blood flow and O 2 uptake were evaluated in 13 anesthetized, ventilated rabbits. Blood flow was measured either directly (Group 1) or by the H 2 clearance method (Group 2). In those animals of Groups 1 and 2 with normal control arterial pH (pHa), ketamine produced a significant increase in cerebral cortical blood flow of 18 and 34%, respectively, but had no effect on cerebral cortical O 3 uptake. However, in rabbits with low control pHa, ketami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 23 publications
0
21
0
2
Order By: Relevance
“…However, it is also possible that changes in CBF occur secondary to changes in MAP (i.e., impaired cerebrovascular autoregulation). 15,16 The present investigation shows that S(+)-ketamine in combination with low-dose propofol did not alter the dynamic cerebrovascular response to a decrease in MAP. As propofol in concentrations used in the present study does not influence cerebrovascular autoregulation, 9 the present data suggest that S(+)-ketamine does not influence dynamic and static autoregulation.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…However, it is also possible that changes in CBF occur secondary to changes in MAP (i.e., impaired cerebrovascular autoregulation). 15,16 The present investigation shows that S(+)-ketamine in combination with low-dose propofol did not alter the dynamic cerebrovascular response to a decrease in MAP. As propofol in concentrations used in the present study does not influence cerebrovascular autoregulation, 9 the present data suggest that S(+)-ketamine does not influence dynamic and static autoregulation.…”
Section: Discussionmentioning
confidence: 45%
“…[12][13][14] This is consistent with studies in awake or N 2 O/O 2 -ventilated animals and humans where racemic ketamine increased CBF along with increases in MAP. 15,16 In contrast, in the presence of anesthetics depressing cerebral metabolism, ketamine did not change or decrease CBF. 1,17,18 This suggests that the effect of ketamine on CBF is related to the pre-existing cerebrovascular tone induced by the background anesthetic technique.…”
Section: Discussionmentioning
confidence: 82%
“…The initial observations of ICP elevations have been related to the cerebral metabolic rate-enhancing effect of ketamine, accompanied by a corresponding increase in CBF, 12,20,23,27,35 as autoregulation is maintained during ketamine anesthesia. Other studies, however, have found no changes 26,31 or even CBF decreases 4,7 following ketamine administration.…”
Section: Discussionmentioning
confidence: 99%
“…ketamine, on CBF. Ketamine has been reported to increase CBF in awake or lightly anesthetized animals and humans (3,4), whereas no changes in CBF (20) or CBF velocity (21,22) were found on ketamine injection when, instead, cerebral depressant anesthetic drugs were used for background anesthesia.…”
Section: Effects Of Confounding Factorsmentioning
confidence: 98%